Circulating extracellular vesicles induce monocyte dysfunction and are associated with sepsis and high mortality in cirrhosis. (1st April 2021) - Baweja, Sukriti; Bihari, Chhagan; Negi, Preeti; Thangariyal, Swati; Kumari, Anupma; Lal, Deepika; Maheshwari, Deepanshu; Singh Maras, Jaswinder; Nautiyal, Nidhi; Kumar, Guresh; Kumar, Anupam; Trehanpati, Nirupama; et al.
Abstract: Background: Sepsis is common in cirrhosis and is often a result of immune dysregulation. Specific stimuli and pathways of inter‐cellular communications between immune cells in cirrhosis and sepsis are incompletely understood. Immune cell‐derived extracellular vesicles (EV) were studied to understand mechanisms of sepsis in cirrhosis. Methods: Immune cell‐derived EV were measured in cirrhosis patients [Child‐Turcotte‐Pugh (Child) score A, n = 15; B n = 16; C n = 43 and Child‐C with sepsis (n = 38)], and healthy controls (HC, n = 11). In vitro and in vivo functional relevance of EV in cirrhosis and associated sepsis was investigated. Results: Monocyte, neutrophil and hematopoietic stem cells associated EV progressively increased with higher Child score ( P < .001)and correlated with liver disease severity indices (r 2 > 0.3, P < .001), which further increased in Child C sepsis than without sepsis( P < .001); monocyte EV showing the highest association with disease stage [ P = .013; Odds ratio‐4.14(1.34‐12.42)]. A threshold level of monocyte EV of 53/µl predicted mortality in patients of Child C with sepsis [Odds ratio‐6.2 (2.4‐15.9), AUROC = 0.76, P < .01]. In vitro EV from cirrhotic with sepsis compared without sepsis, induced mobilization arrest in healthy monocytes within 4 hours ( P = .004), reduced basal oxygen consumption rate ( P < .001) and induced pro‐inflammatory genes ( P < .05). The septic‐EV on adoptive transfer to C57/BL6J mice, induced sepsis‐like condition within 24 h with leukocytopenia ( P = .005), intrahepatic inflammation with increased CD11b + cells ( P = .03) and bone marrow hyperplasia ( P < .01). Conclusion: Extracellular vesicles induce functional impairment in circulating monocytes and contribute to the development and perpetuation of sepsis. High levels of monocyte EV correlate with mortality and can help early stratification of sicker patients.